2012
DOI: 10.1002/adfm.201202015
|View full text |Cite
|
Sign up to set email alerts
|

Double Stimuli‐Responsive Isoporous Membranes via Post‐Modification of pH‐Sensitive Self‐Assembled Diblock Copolymer Membranes

Abstract: Double stimuli‐responsive membranes are prepared by modification of pH‐sensitive integral asymmetric polystyrene‐b‐poly(4‐vinylpyridine) (PS‐b‐P4VP) diblock copolymer membranes with temperature‐responsive poly(N‐isopropylacrylamide) (pNIPAM) by a surface linking reaction. PS‐b‐P4VP membranes are first functionalized with a mild mussel‐inspired polydopamine coating and then reacted via Michael addition with an amine‐terminated pNIPAM‐NH2 under slightly basic conditions. The membranes are thoroughly characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
175
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 203 publications
(184 citation statements)
references
References 45 publications
2
175
0
3
Order By: Relevance
“…Later on it was shown that different additives can support the membrane formation [12][13][14]. Additionally, post-modification of this type of membrane was done and led to superior properties, such as double stimuli-responsivity [15]. This concept was further extended to not only diblock copolymers, but also triblock terpolymers for the fabrication of integral asymmetric membrane via self-assembly SNIPS [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Later on it was shown that different additives can support the membrane formation [12][13][14]. Additionally, post-modification of this type of membrane was done and led to superior properties, such as double stimuli-responsivity [15]. This concept was further extended to not only diblock copolymers, but also triblock terpolymers for the fabrication of integral asymmetric membrane via self-assembly SNIPS [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They exhibit particular properties which are caused by the combination of different blocks most often leading to self-assembled periodic microphase separated structures. The application of block copolymers in modern material science varies from blends [5][6][7][8][9][10][11][12], nanopatterning [13][14][15][16][17][18] to membranes [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…As described in the introduction, the microphase separation of block copolymers in solvent mixtures can be advantageously used for the preparation of integral asymmetric membranes by SNIPS process [42,43,46,57]. In general, the pore structure formation is tremendously influenced by a variety of parameters such as, e.g., evaporation time, solvent mixture, additives like salts, humidity, temperature, etc.…”
Section: Membrane Preparation By Self-assembly and Non-solvent-inducementioning
confidence: 99%
“…[42,43,46,57] In general, the pore structure formation is tremendously influenced by a variety of parameters such as, e.g., evaporation time, solvent mixture, additives like salts, humidity, temperature, etc. [44,[57][58][59].…”
Section: Membrane Preparation By Self-assembly and Non-solvent-inducementioning
confidence: 99%
See 1 more Smart Citation